Effect of the leukotriene receptor antagonist MK-0679 on baseline pulmonary function in aspirin sensitive asthmatic subjects. Issue 12 (December 1993) - Dahlén, B; Margolskee, D J; Zetterström, O; Dahlén, S E
Abstract : BACKGROUND--The cysteinyl leukotrienes (LTC4, LTD4, and LTE4) have been shown to mediate airway obstruction evoked by several factors which trigger asthmatic reactions--for example, allergen and exercise. Accordingly, drugs which block the action or formation of these leukotrienes are being evaluated as a new treatment of asthma. Elevated production of leukotrienes has been reported in asthmatic subjects who are intolerant to aspirin and related nonsteroidal anti-inflammatory drugs. In this study the influence of the specific leukotriene receptor antagonist MK-0679 was tested on basal airway function in asthmatic patients with documented aspirin intolerance. METHODS--The eight subjects in the study had a mean baseline FEV1 of 78% predicted (range 58-99%) and six required treatment with inhaled glucocorticosteroids (400-1200 micrograms budesonide/beclomethasone daily). On two separate days the subjects received either 825 mg MK-0679 or placebo, orally in a double blind, randomised, crossover design. RESULTS--The leukotriene antagonist MK-0679 caused bronchodilation which lasted for at least nine hours. The average peak improvement in FEV1 was 18% above the predrug baseline, but the bronchodilator response varied between 34% and 5% and was found to correlate strongly with the severity of asthma and aspirin sensitivity. CONCLUSIONS--The findings indicate that ongoing leukotriene production may be one cause of persistent airway obstruction in aspirin sensitive asthmatic subjects and that they may benefit from treatment with a leukotriene receptor antagonist.